Walker, Charles F. Shaky Colonialism: The 1746 Earthquake-Tsunami in Lima, Peru, and Its Long Aftermath. Durham: Duke University Press, 2008, 260 pp. - Villa-Flores, Javier (Histórica, 2008)
La reseña no presenta resumen.